2009
DOI: 10.1002/tie.20264
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of FDI determinants in China and India

Abstract: This study explores foreign direct investment (FDI) determinants in China and India and fills the gap in the literature by providing a comprehensive empirical comparison analysis. Two panel data sets and two statistical models are employed to identify the determinants of FDI inflows from home countries worldwide to the two host countries by considering both home and host countries' characteristics. The empirical results show some interesting similarities and differences between the two countries. Market growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 15 publications
3
44
1
Order By: Relevance
“…Furthermore, China invests in countries that are more open and/or have a closer trade relation with China. These results are consistent with the previous findings by Buckley et al (2007), Zheng, (2009), and Zhang -Daly (2011.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, China invests in countries that are more open and/or have a closer trade relation with China. These results are consistent with the previous findings by Buckley et al (2007), Zheng, (2009), and Zhang -Daly (2011.…”
Section: Resultssupporting
confidence: 94%
“…Previous studies, e.g., Grosse -Trevino (1996) and Zheng (2009), have suggested that trade has a strong relation with the amount of a country's ODI, and we thus include the trade variable of China's exports (EXP) to destination countries. Firms prefer to invest in trade markets they are more familiar with, and high trade volumes might indicate a high economic integration between the countries.…”
mentioning
confidence: 99%
“…Reference [25] uses panel data from 117 countries and shows higher corruption levels decrease FDI inflows. Political risk has also been found to be an important determinant of FDI into China and India from the research by [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Institutional factors play an increasingly important role in the location decisions (Zheng, 2009). Institutional changes in FDI regulations can have a major influence on geographic diversification decisions (Peng & Delios, 2006), and many countries have stepped up their bids to attract FDI by implementing favorable policies for foreign investors.…”
Section: Market-supporting Institutionsmentioning
confidence: 99%
“…It is to be expected that political risk will be negatively related to FDI, given that MNEs will be more reluctant to invest in countries that are a high risk or have an unstable environment (Buckley et al, 2007;Zheng, 2009). These arguments would therefore suggest that:…”
Section: Political Riskmentioning
confidence: 99%